Predicting potential Rastrelliger kanagurta fish habitat using MODIS satellite data and GIS modeling: a case study of Exclusive Economic Zone, Malaysia - Shaari N.R; Mustapha M.A. (Penerbit Universiti Kebangsaan Malaysia, 2018)
Remote sensing and GIS are robust tools in detection of fishing grounds which is important in providing fish sustainability for human being. This recent tool allows fishing grounds detection at minimal cost and optimizes effort. The objectives of this study were to investigate the relationship between R. kanagurta fishing grounds with environmental factors and to determine its potential fishing grounds. MODIS derived satellite data of Chl-a and sea surface temperature (SST) and fisheries catch data of 2008 and 2009 were analyzed using suitability index (SI) and generalized additive model (GAM) in the Exclusive Economic Zone (EEZ) off the East Coast of Peninsular Malaysia. Distribution of R. kanagurta was associated with preferred range of 0.20 to 0.30 mg/m3 for Chl-a and 29 to 30°C for SST. GAM indicated that these parameters influenced fish distribution (p<0.001). Potential fishing ground maps derived from the SI and GAM model indicated accuracy at 75% with kappa of 0.7 and accuracy at 87.6% with kappa of 0.8, respectively. This study indicated the capability of GAM as an exploratory tool to map the potential fishing grounds of R. kanagurta in the EEZ waters.